2020
DOI: 10.3390/healthcare8020112
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Mitigating Strategies to Healthcare Access in Indigenous Communities of Canada: A Narrative Review

Abstract: The objective of this review is to document contemporary barriers to accessing healthcare faced by Indigenous people of Canada and approaches taken to mitigate these concerns. A narrative review of the literature was conducted. Barriers to healthcare access and mitigating strategies were aligned into three categories: proximal, intermediate, and distal barriers. Proximal barriers include geography, education attainment, and negative bias among healthcare professionals resulting in a lack of or inadequate immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 32 publications
0
85
0
2
Order By: Relevance
“…Data on Educational level was not available within our database but the 2016 Statcan report identifies income as proportional to education among Saskatchewanians who identify as aboriginal [42]. Further support for the disparity between income, education and access to health care are reported by Nguyen (2020) [43] who identified health care barriers faced by Indigenous Canadians that may have contributed to our findings of higher rates of major and minor LA in all groups (overall, primary and subsequent LA) in younger RI's living in Saskatchewan.…”
Section: Discussionmentioning
confidence: 99%
“…Data on Educational level was not available within our database but the 2016 Statcan report identifies income as proportional to education among Saskatchewanians who identify as aboriginal [42]. Further support for the disparity between income, education and access to health care are reported by Nguyen (2020) [43] who identified health care barriers faced by Indigenous Canadians that may have contributed to our findings of higher rates of major and minor LA in all groups (overall, primary and subsequent LA) in younger RI's living in Saskatchewan.…”
Section: Discussionmentioning
confidence: 99%
“…Stigma and discrimination remain a barrier to accessing mental health services for many Indigenous peoples in Canada (13,45). The values and traditions of Indigenous persons may be poorly understood and their concepts of wellness and ways of knowing sometimes undervalued.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, different Indigenous groups in Canada, such as Métis (6, 10) and urban or off-reserve First Nation communities, can have unique experiences that are often excluded in research and data, and which may require different culturally-based responses. Indigenous people also face many structural barriers due to the legacy of colonialism in a healthcare system where western knowledge is valued over Indigenous knowledge, trauma-informed care is not consistently practiced, and negative bias from care providers persists due to lack of cultural competency (6, [11][12][13].…”
Section: Indigenous Peoples' Historical and Contemporary Experiences With Access To Mental Healthcarementioning
confidence: 99%
“…These are the biggest challenges for the health administrators of the Peruvian government. In a recent review [ 43 ], the authors reported some of the most important healthcare strategies used for indigenous groups. Some examples include improving essential infrastructure (healthcare facilities in remote areas), increasing access to education, enhancing cultural sensitivity for healthcare professionals, incentives for healthcare professionals, the collaboration of indigenous communities with universities, and improving social accessibility, among others.…”
Section: Discussionmentioning
confidence: 99%